Analysis of nutritional contents, microbiological contamination and presence of aflatoxins in unpacked feeds sold for pet-birds in istanbul - Serol Korkmaz; Irem Omurtag Korkmaz; Didem Hilkat Aksakal; Tanay Bilal (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aim to determine the nutritional efficiency, microbiological quality and aflatoxin contents of unpacked pet-bird feeds sold in Istanbul. Materials and Methods: A total of 102 unpacked feed samples sold for canary (n=35), budgerigar (n=37) and parrot (n=30) were collected from different districts in Istanbul. All the samples, consist of seed mixtures, were analysed regard to their nutritional content, microbiological quality and presence of aflatoxins. Results: Crude protein (CP), crude fat (CF) and metabolizable energy (ME) levels of the budgerigar feeds were met the nutritional requirements. However, nutritional contents (CP, CF, ME) of the canary and parrot feeds were higher than their requirements. In the microbiological analysis, Coliform group of bacteria were isolated from ~40% of budgerigar and canary feeds (3.19 ± 0.16 and 3.25 ± 0.11 log cfu/g, respectively), while isolated from all of the parrot feeds (100%; mean 3.43±0.58 log cfu/g). None of the 102 feeds were contaminated with Salmonella. Mould content of the feeds (100%) was ranging from 3 to 5.5 log cfu/g. Aflatoxin content (B1, B2, G1, G2) was not detected in feed samples. Conclusion: Regarding to the microbiological results of seed mixtures no threat is found for pet birds. However, it is assumed that nutritional imbalance formulation of canary and parrot feeds may affect adversely the pet birds health.